2021
DOI: 10.3389/fsurg.2021.590448
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Recurrence After Radical Nephroureterectomy of Upper Urinary Tract Urothelial Carcinoma: A Large Population-Based Investigation of Clinicopathologic Characteristics and Survival Outcomes

Abstract: Background: Of patients with upper urinary tract urothelial carcinoma (UTUC), 22–47% developed bladder recurrence after radical nephroureterectomy. Furthermore, the effect of surgery for UTUC-bladder cancer (BC) has not been well validated. The aim of this study was to assess the impact of standard primary BC surgical strategy on survival of patients diagnosed with UTUC-BC.Patients and Methods: A total of 676 UTUC-BC patients and 197,753 primary BC patients diagnosed from 2004 to 2016, were identified based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…However, recent data suggest that current primary UBC surgical guidelines are not entirely appropriate for UTUC-UBC patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data suggest that current primary UBC surgical guidelines are not entirely appropriate for UTUC-UBC patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Impact of previous, simultaneous or intravesical recurrence bladder cancer on prognosis of upper tract urothelial carcinoma after nephroureterectomy: a large population-based study 22-47% of UTUC patients may experience intravesical recurrence (IVR) after nephroureterectomy (RNU) (4,5). Currently, the impact of previous, simultaneous or IVR on the prognosis of UTUC is controversial.…”
Section: Original Articlementioning
confidence: 99%
“…Nevertheless, several studies revealed that UTUC patients with concomitant or bladder cancer history had worse prognosis, and was an independent risk factor (2,9,10). Meanwhile, IVR was also reported to have an adverse effect on the prognosis of UTUC (2,5,11). In contrast, studies showed IVR after RNU did not affect the prognosis of UTUC (12,13).…”
Section: Original Articlementioning
confidence: 99%
“…RNU with bladder cuff excision is the standard of care for non-metastatic UTUC (15). Despite recent advances in the care of urothelial carcinoma, the rate of BTR following RNU remains high (4,7,16,17). Multiple studies have examined the risk factors for BTR, but results vary significantly.…”
Section: Introductionmentioning
confidence: 99%